The evolving universe and the origin of life : the search for our cosmic roots - Teerikorpi, Pekka ; Valtonen ,Mauri ; Lehto, Kirsi ; Lehto,Harry ; Byrd, Gene ; Chernin, Arthur (Springer, 2017)
The Evolving Universe and the Origin of Life describes, complete with fascinating biographical details of the thinkers involved, the ascent to the metaphorical shoulders accomplished by the greatest minds in history. For the first time, a single book can take the reader on a journey through the history of the universe as interpreted by the expanding body of knowledge of humankind. From subatomic particles to the protein chains that form life, and expanding in scale to the entire universe, this book covers the science that explains how we came to be. The Evolving Universe and the Origin of Life contains a great breadth of knowledge, from astronomy to physics, from chemistry to biology. It includes over 350 figures that enhance the comprehension of concepts both basic and advanced, and is a non-technical, easy-to-read text at an introductory college level that is ideal for anyone interested in science as well as its history.